Biological activities and chemical constituents of ferula anatolica boiss - Kurtoğlu, Sezin; Tan, Nur Amanina Syariff; Meriçli, Ali Hikmet; Miski, Mahmut (Georg Thieme Verlag Kg, 2013)
Genus Ferula has about 185 species and widely distributed through out Central Asia, China, Afghanistan, India, Syria, Palestine, Israel, North Africa, North America, South-West and Central Europe. Currently, 23 species and 4 subspecies of Ferula are known from Turkey and 12 of them are endemic. Chemical composition of 70 Ferulaspecies were investigated by phytochemical studies so far; glucuronic acid, galactose, arabinose, rhamnose, sulphur containing compounds, coumarins, sesquiterpenes, sesquiterpene coumarins, sesquiterpene lactones and daucane esters (Miski, 1985, Ahmed, 1999) were isolated. In this study, Ferula anatolica Boiss. which is endemic species growing in Turkey, have been investigated for its chemical constituents and cytotoxic and antioxidant activity. The air dried and powdered underground parts of plant extracted with soxhlet apparatus with petroleum ether, dichloromethane and methanol. The petrolerum ether extract of F. anatolica was used for isolation studies. By means of a serial chromatographic studies performed on the extract five sesquiterpene derivatives compounds were isolated. The structures of compounds were elucidated using spectroscopic methods.
WOS: 000209339700355
Keywords: Biological; Activities and Chemical; Constituents of Ferula; Anatolica Boiss